التوظيف السياسي للقضايا والتطورات الدولية كذريعة للتدخل الإنساني - صيوح لؤي; طه طه; أبوحسين لؤي (Latakia University Journal - Economic and Legal Sciences Series, 2018)
إن الدول الكبرى تحاول وبشكل متواصل البحث عن طرق مُبتكرة تتيح لها التدخل المشروع في شؤون الدول الأخرى لذلك عملت جاهدة لإيجاد وطرح مفاهيم ومظاهر مُستحدثة على الساحة الدولية، كمفاهيم الدول الفاشلة، الفوضى الخلاقة، الربيع العربي، والعمل على توظيفها سياسياً بما يتيح لها التدخل في الدول الأخرى، وقد خلص البحث إلى أن الدول الكبرى، وعلى رأسها الولايات المتحدة الأمريكية، تعمل على استغلال قضايا حقوق الإنسان، ومسألة تهديد السلم والأمن الدوليين وتحويلهما إلى أداة للابتزاز والضغط على بعض الدول دون غيرها لتبرير فكرة التدخل الإنساني حيث تُسخر هذه الدول عوامل قوتها ونفوذها للتأثير على منظمة الأمم المتحدة وتوظيفها وتكييف قرارتها بما يخدم مصالحها ومصالح حلفائها الغربيين، تاركين الدول الضعيفة تعيش حالات من النزاع والفوضى والفشل. The great powers are constantly trying to find innovative ways to intervene in the affairsof other countries. Therefore, I have worked hard to find and introduce new concepts and manifestations on the international scene, such as the failed states, the creative chaos, the Arab Spring, The research concluded that the major countries, especially the United States of America, are working to exploit human rights issues and to threaten international peace and security and turn them into a tool of blackmail and pressure on some countries to justify the idea of ​​humanitarian intervention. Its power and influence to influence and employ the United Nations and adapt its decision to serve its own interests and the interests of its Western allies, leaving weak states living in situations of conflict, chaos and failure.